Replace the values of h and k to create the equation of the transformed function.
![Replace the values of h and k to create the equation of the transformed function class=](https://us-static.z-dn.net/files/da3/e68abe3b889633002cceff1b1ac9ddbd.png)
Answer:
Step-by-step explanation:
y = ∛x is the original function, which has its center in the origin
As we see the function y = ∛(x - h) - x has its center moved to the point (4, -1)
This gives us h = 4 and k = 1, as negative h indicates translation to the right and negative k- translation down